2009
DOI: 10.1017/s0022215109991563
|View full text |Cite
|
Sign up to set email alerts
|

Necrobiotic xanthogranuloma of the parotid gland

Abstract: Necrobiotic xanthogranuloma may clinically mimic commoner tumours such as Warthin's tumour. Once diagnosed, the clinician should be wary of extracutaneous manifestations and paraproteinaemias. Because of the variability of presentation, there is no consensus on the best treatment for necrobiotic xanthogranuloma, which may include surgery, chemotherapy, interferon, plasmapheresis and radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…But in our case first-time FNAC did and found Xanthogranulomatous inflammation on cytology. Some studies described XG inflammation associated with Warthin's tumour [2][3]6]. In our case aetiology not clear for XG inflammation.…”
Section: Malek Et Al Reported a Series Of 26 Patients Withcontrasting
confidence: 58%
See 1 more Smart Citation
“…But in our case first-time FNAC did and found Xanthogranulomatous inflammation on cytology. Some studies described XG inflammation associated with Warthin's tumour [2][3]6]. In our case aetiology not clear for XG inflammation.…”
Section: Malek Et Al Reported a Series Of 26 Patients Withcontrasting
confidence: 58%
“…It commonly seen in kidney, causative agents exact not known, XGI believed to develop in the setting of a suppurative infection with renal outflow obstruction [1]. Mostly studies demonstrated XG inflammation in parotid gland with slow-growing mass [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In the systematic review, the initial search yielded 1199 records, 151 of which were included (Figure). These reports described 201 patients with NXG, with demographics, comorbidities, and clinical features (detailed in the eTable in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Common sites include the periocular area and thorax [1]. NXG is rare in the head and neck area, and there has been only one case reported in the salivary gland [4]. NXG has characteristic histologic features, showing clusters of foamy xanthomatous macrophages, granulomas, and giant cells of foreign body type or Touton-type, cholesterol clefts, and necrobiosis [2].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of NXG is variable and unpredictable, and recurrence of the lesion and/or multiple dissemination have been reported at other sites [13,14]. Other cases have shown systemic involvement, including hematologic malignancy and cardiac myopathy [1,4,13]. About 20% of patients in a previous study developed hematologic malignancy during the 11-year follow-up period [15].…”
Section: Discussionmentioning
confidence: 99%